A microwave synthesis coal-based carbon / ferromagnetic metal composite electromagnetic absorption material and method
Through microwave in-situ synthesis technology, raw coal and transition metal are formed under microwave action to form coal-based carbon/ferromagnetic metal composite materials, solving the problems of coal utilization and low-frequency microwave pollution, and achieving efficient and low-cost coal conversion and good quality electromagnetic absorption performance.
Patent Information
- Application Number
- CN202010535921.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-06-12
AI Technical Summary
The existing technology is difficult to achieve efficient and low-cost utilization of coal and effectively control low-frequency microwave pollution. The traditional coal conversion process is complex and not suitable for large-scale production. Electromagnetic absorbing materials have poor effect on low-frequency microwave treatment.
Using microwave in situ synthesis method, raw coal reacts with the chloride or sulfate of transition group metal iron, cobalt, nickel under microwave action to form a coal-based carbon/ferromagnetic metal composite electromagnetic absorption material, using potassium hydroxide and deionized water Perform uniform mixing and catalysis to form metal oxides or alloys with magnetic media.
It realizes high added value utilization of coal, simplifies the process flow, reduces costs, and the prepared materials have good low-frequency microwave absorption performance, are suitable for industrial promotion, and show excellent absorption effect in the civil microwave frequency band.
Smart Images

Figure CN111683512B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal-based carbon composite electromagnetic absorption materials, and specifically relates to a coal-based carbon / ferromagnetic metal composite electromagnetic absorption material synthesized in situ by microwaves using coal as a carbon source and a preparation method thereof. Technical Background
[0002] Coal is a natural resource that people have relied on for survival for a long time and is widely used in power generation, coking, coal chemical industry and other fields. The traditional way of using coal is single. During its combustion, gasification and other transformation processes, the waste and waste residues produced are also easy to pollute the environment. Therefore, there is an urgent need for a new clean and efficient method for utilizing coal. At present, many scholars have studied a variety of coal-to-carbon techniques. Common technologies include: preparing porous activated carbon using alkaline activation method at high temperature; using catalysts to prepare coal-based carbon nanomaterials such as carbon nanotubes and carbon nanospheres. Chinese patent CN107376836A prepares high-performance activated carbon from coal particles and ferrocene at high temperature, and the synthesis temperature is 800-1200℃. Chinese patent CN110562960A uses catalysts to prepare coal-based carbon nanotubes in a nitrogen atmosphere, and the synthesis process is relatively complicated. Although the preparation of these coal-based carbon materials increases the added value of coal, it is difficult to achieve mass production due to complex processes, high synthesis temperatures, and long process cycles.
[0003] In recent years, with the rapid development of science and technology, large-scale equipment and electronic products usually radiate electromagnetic waves within a certain range, which is harmful to human health. Electromagnetic absorption materials convert incident waves into heat inside the material through various loss mechanisms, which can effectively reduce microwave pollution. Ferromagnetic metals are widely used in the preparation process of absorbing materials due to their high saturation magnetization. Chinese patent CN101546610A heat treats ceramic metals with ferromagnetic metal coatings on the surface under hydrogen or argon conditions to obtain ceramic whiskers / ferromagnetic metal composite absorbing materials. Chinese patent CN105896099A uses porous carbon balls and ferromagnetic metal ion salts to sinter in a nitrogen atmosphere to obtain absorbing materials. These syntheses usually have high requirements for environmental gases, long heat treatment time, high processing costs, and are not suitable for mass production. In addition, although electromagnetic absorption materials have achieved certain achievements, low-frequency microwaves with strong diffraction capabilities are still difficult to handle. Summary of the invention
[0004] The present invention aims to realize high added value utilization of coal and control the problem of low-frequency microwave pollution, and provides a microwave synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material and method.
[0005] The present invention adopts the following technical solutions:
[0006] A microwave-synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material, wherein the coal-based carbon / ferromagnetic metal composite material is formed by in-situ reaction of raw coal and chloride, sulfate or nitrate of at least one transition metal iron, cobalt and nickel under the action of microwaves; the magnetic medium of the coal-based carbon / ferromagnetic metal composite material comprises a metal oxide formed by chloride, sulfate or nitrate of the transition metal iron, cobalt and nickel, or a coexistence form of a metal alloy of the metal oxide and at least two metals of the transition metal iron, cobalt and nickel.
[0007] Preferably, the method for preparing the microwave synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material comprises the following steps:
[0008] S1. Crushing and screening the raw coal into particles of 2-5 mm in dry air;
[0009] S2. Weigh raw coal, transition metal salt and potassium hydroxide in proportion, add deionized water, stir and mix the raw coal, transition metal salt and potassium hydroxide to obtain a mixed raw material; the transition metal salt refers to any chloride, sulfate or nitrate of at least one metal in the transition metal group iron, cobalt and nickel;
[0010] S3. The mixed raw materials are placed in a microwave reaction device, reacted to 700 ° C, cooled to room temperature after the reaction is completed, and then the reaction product is taken out;
[0011] S4. Wash and filter the reaction product with deionized water, and dry it to obtain a coal-based carbon / ferromagnetic metal composite electromagnetic absorption material.
[0012] Preferably, the raw coal is coal of any type having a fixed carbon content of more than 75 wt% after washing.
[0013] Preferably, in step S2, a mixture of raw coal and transition metal salt is weighed, the mass of the raw coal is X, the mass of the transition metal salt is (1-X), potassium hydroxide is weighed, the mass of the potassium hydroxide is 2X; wherein 0<X<1.
[0014] Preferably, in step S2, the volume of the deionized water is 10-25 ml of deionized water per 10 g of the mixture of the raw coal and the transition metal salt.
[0015] Preferably, in step S3, the microwave reaction device uses a frequency of 915 MHz or 2.45 GHz.
[0016] Preferably, in step S3, the microwave reaction device heats the uniformly mixed raw materials to a temperature of 700° C. at a fixed power, and the microwave reaction device is turned off to stop heating after the uniformly mixed raw materials reach the reaction temperature.
[0017] Preferably, in step S3, the uniformly mixed raw materials are contacted with air in a microwave reaction device for reaction, and are cooled in air after the reaction is completed.
[0018] The beneficial effects of the present invention are:
[0019] 1) According to statistics, my country has huge coal reserves, ranking third in the world. The traditional way of using coal not only has low output value, but also easily causes damage to the environment. The present invention uses coal as a carbon source to prepare electromagnetic absorption materials. The carbonization effect of coal is good, and it provides methods and experience for developing new application paths for coal. The method utilizes the raw material characteristics of coal rich in carbon sources, which can make full use of coal without generating any pollutants, thus realizing high added value utilization of coal.
[0020] 2) The present invention adopts microwave in-situ synthesis technology, and utilizes the coupled thermal effect generated by the material's own absorption of microwaves, which has the advantages of homogeneity and speed. During the synthesis process, microwaves generate heat inside the material, causing the heat to expand from the inside to the outside, ensuring that the material is heated evenly. Microwaves replace heat to be transferred through the medium, effectively avoiding energy loss during the transfer process, and achieving a better heating effect. The present invention uses a microwave reaction device with a microwave frequency band of 915MHz and 2.45GHz to in-situ synthesize coal-based carbon / ferromagnetic metal composite electromagnetic absorption materials, which simplifies the traditional composite process. The raw materials are heated and reacted to the required temperature and then naturally cooled without insulation, effectively shortening the synthesis time and reducing the synthesis cost, which is convenient for industrial promotion. Since the microwave frequency bands of 915MHz and 2.45GHz are also widely used in civilian microwave devices, the application scope of this method is further expanded;
[0021] 3) Since microwave synthesis is selective, different degrees of heat will be generated according to the different dielectric losses of the materials. The present invention uses coal as the carbon source and utilizes the certain dielectric properties of coal to fully respond to microwaves. Thanks to the homogeneity of coal heating, the prepared composite material has a rough grid-like pore structure surface and a large specific surface area. Experiments have shown that the coal-based carbon / ferromagnetic metal composite electromagnetic absorption material prepared by this method has good microwave absorption performance at low frequencies.
[0022] 4) Electromagnetic absorption materials mainly have two major loss mechanisms: dielectric loss and magnetic loss; transition metals iron, cobalt, and nickel are ferromagnetic. Under the action of microwaves, the reducing gas released by coal during carbonization can make the salt compounds of iron, cobalt, and nickel form metal oxides. When multiple salt compounds of ferromagnetic metals exist at the same time, metal alloys of the above multiple ferromagnetic metals and metal oxides can also coexist in two forms. The metal oxides of iron, cobalt, and nickel and the metal alloys between them can act as the magnetic medium of the composite material, increase the magnetic loss of the composite material, and enhance the electromagnetic absorption performance.
[0023] 5) The potassium hydroxide used in the method plays an alkali activation and catalytic role in the reaction system. Deionized water dissolves potassium hydroxide and transition metal salts, and makes them fully and evenly mixed with raw coal to form a mixture reaction system that is bonded together. Potassium hydroxide releases heat when dissolved in deionized water, and part of the excess deionized water can be evaporated, so that the mixture reaction system is not too humid. Since microwave heating accelerates the reaction time, the mixture reaction system using the method does not require an additional drying step, and the subsequent experimental operation can be directly carried out after the raw materials are mixed, which is efficient and safe. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the coal-based carbon / ferromagnetic metal composite electromagnetic absorption material prepared in the present invention: the surface of the coal-based carbon has abundant micron-sized pores, and most of the metal particles are embedded in the pores.
[0025] Figure 2 The XRD graphs of the coal-based carbon / ferromagnetic metal composite electromagnetic absorption materials prepared in Examples 1, 2, and 3 of the present invention, and the XRD graph of the coal-based carbon / ferromagnetic metal composite material synthesized in a nitrogen atmosphere at 700°C in a tube furnace in Comparative Example 1 using a conventional synthesis method, wherein the horizontal axis represents the diffraction angle and the vertical axis represents the intensity. It can be seen from the figure that the coal-based carbon / ferromagnetic metal composite material synthesized in situ using microwaves has a more obvious carbon characteristic peak at 15-25°, indicating that the carbonization effect is better.
[0026] Figure 3 , 4 and 5 are respectively reflection loss graphs of the coal-based carbon / ferromagnetic metal composite electromagnetic absorption material prepared by using anthracite and metal chloride in different proportions in Examples 1, 2 and 3 of the present invention and mixed with molten paraffin in a mass ratio of 1:1 and measured by using AV3672B-S vector network analyzer at 2-18 GHz, wherein the horizontal axis represents frequency and the vertical axis represents reflection loss.
[0027] Figure 6 This is a comparison chart of reflection loss measured at 218 GHz by AV3672B-S vector network analyzer, in which the coal-based carbon / ferromagnetic metal composite material synthesized in a nitrogen atmosphere at 800°C in a tubular furnace by a conventional synthesis method and mixed with molten paraffin in a mass ratio of 1:1, wherein the horizontal axis represents frequency and the vertical axis represents reflection loss. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is described in more detail below in conjunction with the embodiments and comparative examples:
[0029] Embodiment 1:
[0030] The method comprises the following steps: weighing 10 g of anthracite: analytically pure nickel chloride hexahydrate: analytically pure ferric chloride hexahydrate in a mass ratio of 10:7:3, and weighing potassium hydroxide in a mass ratio of anthracite: potassium hydroxide of 1:2 as a standard theoretical formula; crushing and sieving the anthracite to a particle size of 2-5 mm on an air-dried basis, stirring and mixing the treated anthracite with analytically pure nickel chloride hexahydrate, analytically pure ferric chloride hexahydrate and potassium hydroxide in 15 ml of deionized water to obtain a mixed raw material; heating the mixed raw material to 700° C. using a WY3L type microwave reactor (actual power 2700 W) with a frequency of 915 MHz, cooling the raw material to room temperature and taking it out; washing and filtering the reaction product with deionized water, and drying the product to obtain a coal-based carbon / ferromagnetic metal composite electromagnetic absorption material.
[0031] In the above experiment, deionized water dissolves potassium hydroxide, nickel chloride hexahydrate, and ferric chloride hexahydrate, and mixes them with the raw coal fully and evenly to form a cohesive mixture reaction system; potassium hydroxide releases heat when dissolved in deionized water, and the excess deionized water evaporates, so that the mixture reaction system is not too moist, and subsequent experimental operations can be carried out directly after the raw materials are mixed.
[0032] Performance test results: Figure 3 The reflection loss in the range of 2-18 GHz is tested in this embodiment according to the coal-based carbon / ferromagnetic metal composite electromagnetic absorption material: paraffin wax = 1:1 (mass ratio). It can be seen from the figure that the prepared coal-based carbon / ferromagnetic metal composite electromagnetic absorption material has a minimum reflection loss of less than -10 dB (absorption rate greater than 90%) at different thicknesses, and has a maximum effective absorption bandwidth of 3.34 GHz, and a minimum reflection loss of -43.36 dB at 5.20 GHz.
[0033] Embodiment 2:
[0034] The method comprises the following steps: weighing 10 g of anthracite: analytically pure nickel chloride hexahydrate: analytically pure ferric chloride hexahydrate in a mass ratio of 10:5:5, and weighing potassium hydroxide in a mass ratio of anthracite: potassium hydroxide of 1:2 as a standard theoretical formula; crushing and sieving the anthracite to a particle size of 2-5 mm on an air-dried basis, stirring and mixing the treated anthracite with analytically pure nickel chloride hexahydrate, analytically pure ferric chloride hexahydrate and potassium hydroxide in 15 ml of deionized water to obtain a mixed raw material; heating the mixed raw material to 700° C. using a WY3L type microwave reactor (actual power 2700 W) with a frequency of 915 MHz, cooling the raw material to room temperature and taking it out; washing and filtering the reaction product with deionized water, and drying the product to obtain a coal-based carbon / ferromagnetic metal composite electromagnetic absorption material.
[0035] Performance test results: Figure 4The reflection loss in the range of 2-18 GHz is tested according to the coal-based carbon / ferromagnetic metal composite electromagnetic absorption material: paraffin wax = 1:1 (mass ratio) in this embodiment. It can be seen from the figure that the prepared coal-based carbon / ferromagnetic metal composite electromagnetic absorption material has a minimum reflection loss of less than -10 dB (absorption rate greater than 90%) at different thicknesses, and has a maximum effective absorption bandwidth of 3.03 GHz, a reflection loss value of less than -20 dB in the thickness range of 3-5 mm, and a minimum reflection loss of -51.66 dB at 5.52 GHz.
[0036] Embodiment 3:
[0037] The method comprises the following steps: weighing 10 g of anthracite: analytically pure nickel chloride hexahydrate: analytically pure ferric chloride hexahydrate in a mass ratio of 10:3:7, and weighing potassium hydroxide in a mass ratio of anthracite: potassium hydroxide of 1:2 as a standard theoretical formula; crushing and sieving the anthracite to a particle size of 2-5 mm on an air-dried basis, stirring and mixing the treated anthracite with analytically pure nickel chloride hexahydrate, analytically pure ferric chloride hexahydrate and potassium hydroxide in 15 ml of deionized water to obtain a mixed raw material; heating the mixed raw material to 700° C. using a WY3L type microwave reactor (actual power 2700 W) with a frequency of 915 MHz, cooling the raw material to room temperature and taking it out; washing and filtering the reaction product with deionized water, and drying the product to obtain a coal-based carbon / ferromagnetic metal composite electromagnetic absorption material.
[0038] Performance test results: Figure 5 The reflection loss in the range of 2-18 GHz is tested according to the coal-based carbon / ferromagnetic metal composite electromagnetic absorption material: paraffin wax = 1:1 (mass ratio) in this embodiment. It can be seen from the figure that the prepared coal-based carbon / ferromagnetic metal composite electromagnetic absorption material has a minimum reflection loss of less than -10 dB (absorption rate greater than 90%) at different thicknesses, and has a maximum effective absorption bandwidth of 2.89 GHz, and a minimum reflection loss of -40.10 dB at 5.68 GHz.
[0039] Comparative Example 1:
[0040] Weigh 10g of anthracite: analytical pure nickel chloride hexahydrate in a mass ratio of 1:1, and weigh potassium hydroxide in a mass ratio of anthracite: potassium hydroxide of 1:2 as a standard theoretical formula; crush and sieve the anthracite to a particle size of 2-5mm under air drying, stir and mix the treated anthracite with analytical pure nickel chloride hexahydrate, analytical pure ferric chloride hexahydrate, and potassium hydroxide in 15ml of deionized water, and dry them in a vacuum oven at 100°C for 24h to obtain a mixed raw material; use a tubular furnace to heat the mixed raw material to 550°C at 5°C / min for 2h in a nitrogen atmosphere, then heat it to 800°C at 2°C / min for 2h, cool it to room temperature and take it out. Wash the reaction product with deionized water and dry it to obtain a coal-based carbon / nickel composite electromagnetic absorption material.
[0041] In the above experiment, the role of potassium hydroxide is the same as that of Examples 1, 2, and 3. In order to obtain a suitable carbonized structure using conventional methods, the final reaction temperature needs to be 800°C. Since the tubular furnace has a long insulation time, for the safety of the system and sufficient reaction, the mixed reactants need to be dried in advance before subsequent test operations.
[0042] Performance test results: Figure 6 The reflection loss in the range of 2-18 GHz is tested in this comparative example according to the coal-based carbon / nickel composite electromagnetic absorption material: paraffin wax = 1:1 (mass ratio). It can be obtained from the figure that the coal-based carbon / nickel composite electromagnetic absorption material prepared in this comparative example has a minimum reflection loss of less than -10 dB (absorption rate greater than 90%) at different thicknesses, and has a maximum effective absorption bandwidth of 3.53 GHz, and a minimum reflection loss of -42.49 dB at 13.68 GHz.
[0043] Microwaves within the range of 2-18 GHz are divided into multiple bands according to frequency. From the analysis of the experimental results of Example 1, Example 2, Example 3 and Comparative Example 1, it can be seen that the coal-based carbon / ferromagnetic metal composite absorption material prepared in the embodiment of the present application has good microwave absorption performance in the C band (4-8 GHz), and the absorption frequency is much lower than the Ku band (12-18 GHz) where the coal-based carbon / nickel composite electromagnetic absorption material prepared in the comparative example has the best microwave absorption performance, which proves that the present invention has good absorption capacity for low-frequency microwaves.
[0044] The above implementation modes are only used to illustrate the technical solutions of the present invention, but not to limit the present invention. Although the present invention has been described in detail with reference to the above implementation modes, those skilled in the art should understand that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A microwave synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material, Features: The coal-based carbon / ferromagnetic metal composite electromagnetic absorption material is formed by in-situ reaction of raw coal and any chloride salt, sulfate salt or nitrate salt of at least one metal among transition metals iron, cobalt and nickel under the action of microwaves; the magnetic medium of the coal-based carbon / ferromagnetic metal composite electromagnetic absorption material includes metal oxides formed by chloride salts, sulfate salts or nitrate salts of the transition metals iron, cobalt and nickel, or a coexistence form of a metal alloy of the metal oxide and at least two metals among the transition metals iron, cobalt and nickel.
2. A method for preparing a microwave-synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material as claimed in claim 1, Features Here are the steps: S1. Crushing and screening the raw coal into particles of 2-5 mm in dry air; S2. Weigh raw coal, transition metal salt and potassium hydroxide in proportion, add deionized water, stir and mix the raw coal, transition metal salt and potassium hydroxide to obtain a mixed raw material; the transition metal salt refers to any chloride, sulfate or nitrate of at least one metal in the transition metal group iron, cobalt and nickel; S3. The mixed raw materials are placed in a microwave reaction device, reacted to 700 ° C, cooled to room temperature after the reaction is completed, and then the reaction product is taken out; S4. Wash and filter the reaction product with deionized water, and dry it to obtain a coal-based carbon / ferromagnetic metal composite electromagnetic absorption material.
3. A method for preparing a microwave-synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material as claimed in claim 2, Features: The raw coal is any type of coal with a fixed carbon content of more than 75wt% after washing.
4. The method for preparing a microwave-synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material as claimed in claim 2, Features: In step S2, a mixture of raw coal and transition metal salt is weighed, the mass of the raw coal is X, and the mass of the transition metal salt is (1-X), and potassium hydroxide is weighed, and the mass of the potassium hydroxide is 2X; wherein 0<X<1.
5. A method for preparing a microwave-synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material as claimed in claim 4, Features: In the step S2, the volume of the deionized water is 10-25 ml of deionized water per 10 g of the mixture of the raw coal and the transition metal salt.
6. A method for preparing a microwave-synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material as claimed in claim 2, Features: In step S3, the microwave reaction device uses a frequency of 915 MHz or 2.45 GHz.
7. A method for preparing a microwave-synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material as claimed in claim 2, Features: In step S3, the microwave reaction device heats the uniformly mixed raw materials at a fixed power to a reaction temperature of 700° C. After the uniformly mixed raw materials reach the reaction temperature, the microwave reaction device is turned off to stop heating.
8. The method for preparing a microwave-synthesized coal-based carbon / ferromagnetic metal composite electromagnetic absorption material as claimed in claim 2, Features: In step S3, the uniformly mixed raw materials are contacted with air in a microwave reaction device for reaction, and are cooled in air after the reaction is completed.
Citation Information
Patent Citations
Ceramic whisker / ferromagnetic metal composite wave-absorbing material and preparation method thereof
CN101546610A
Method for preparing porous carbon ball composite absorbing material loaded with magnetic metal element
CN105896099A
Coaly magnetic particle activated carbon preparation method
CN107376836A
Preparation and purification method of coal-based carbon nanotubes
CN110562960A
Preparation of surface load magnetic alloy particle carbon nano-tube composite material
CN101503579A
